Fundamentals of the Physics of Solids Volume 1: Structure and Dynamics - Sólyom, Jenö.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book is the first of a three-volume series written by the same author that aims to deliver a comprehensive and self-contained account of the vast field of solid-state physics. It goes far beyond most classic texts in the presentation of the properties of solids and experimentally observed phenomena, along with the basic concepts and theoretical methods used to understand them and the essential features of various experimental techniques. The first volume deals with the atomic and magnetic structure and the dynamics of solids, the second with those electric properties that can be understood in terms of the one-particle approximation, and the third with the effects due to interactions and correlations among electrons. This volume covers four major topics. After a brief history of solid-state physics, the introductory part presents the classification of condensed phases, describes the basic features of atoms as building blocks of solids, and analyzes how atoms bind together to form solids. The second part deals with structural aspects. The symmetries of crystalline solids and their consequences are covered in detail. Deviations from crystalline order either due to defects or in form of quasicrystalline or noncrystalline structures are also discussed. The third part is devoted to the theoretical description and experimental observation of lattice vibrations. Finally, magnetism due to localized magnetic moments is treated both phenomenologically and quantum mechanically. The text provides ample material for upper-level undergraduate and graduate courses. The book also serves as a valuable reference for researchers in the field of condensed matter physics.
The Structure of Condensed Matter -- The Building Blocks of Solids -- Bonding in Solids -- Symmetries of Crystals -- Consequences of Symmetries -- The Structure of Crystals -- Methods of Structure Determination -- The Structure of Real Crystals -- The Structure of Noncrystalline Solids -- Dynamics of Crystal Lattices -- The Quantum Theory of Lattice Vibrations -- The Experimental Study of Phonons -- Magnetically Ordered Systems -- Elementary Excitations in Magnetic Systems.
Keywords: Condensed matter; Condensed Matter Physics